# Given the functions #F(x)=x+4# and #G(x)=2x^2+4# what is f(g(x))?

To find ( f(g(x)) ), you first need to find the expression for ( g(x) ), and then substitute it into ( f(x) ) wherever you see ( x ).

Given ( g(x) = 2x^2 + 4 ) and ( f(x) = x + 4 ), substitute ( g(x) ) into ( f(x) ):

[ f(g(x)) = f(2x^2 + 4) ]

Now, replace ( x ) in ( f(x) ) with ( 2x^2 + 4 ):

[ f(g(x)) = (2x^2 + 4) + 4 ]

[ f(g(x)) = 2x^2 + 8 ]

So, ( f(g(x)) = 2x^2 + 8 ).

By signing up, you agree to our Terms of Service and Privacy Policy

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7